Long‐term progression of viral load and serum markers of fibrosis among treated and untreated patients with chronic hepatitis B. Issue 6 (30th May 2017) - Li, Jia; Gordon, Stuart C; Rupp, Loralee B; Zhang, Talan; Trudeau, Sheri; Holmberg, Scott D; Moorman, Anne C; Spradling, Philip R; Teshale, Eyasu H; Boscarino, Joseph A; Daida, Yihe G; Schmidt, Mark A; et al.
Abstract: Background and Aims: Antiviral therapy for patients with hepatitis B (HBV) infection is generally deferred for "immune inactive" patients, although longitudinal changes in viral load and liver fibrosis remain understudied in this population. Likewise, in treated patients, the temporal relationship between changes in viral load and liver fibrosis is not well characterized. Using data from the chronic hepatitis cohort study, the study investigated viral load and the Fibrosis‐4 index (FIB4, a serum‐based marker of liver fibrosis) trajectories in both untreated and treated HBV patients. Materials and Methods: We applied a bivariate, piecewise, linear spline, mixed‐effects modeling approach to data from 766 HBV patients (342 untreated, 424 treated). Treatment selection bias was adjusted using propensity scores. Multiple sensitivity analyses were used to confirm results in untreated patients. Results: Among all untreated patients, FIB4 began to increase by 0.9% per month (11% per year; P < 0.05) at 28 months post‐index date, suggesting fibrosis progression. Significant FIB4 progression was also observed in a subgroup analysis of "immune inactive" untreated patients. In treated patients, viral load declined 31.8% per month ( P < 0.05) for the first 5 months after treatment initiation, and 1.4–1.7% per month ( P < 0.05) thereafter. At 5 months after treatment initiation, FIB4 began to decline 0.5% per month ( P < 0.05), stabilizing at 28 months. Conclusion: Among untreated HBV patients, FIB4 gradually increases over time, suggesting fibrosis progression, even in those patients designated as immune inactive. In treated patients, antiviral therapy results in a rapid decline in viral load followed by a delayed decline in markers of liver fibrosis.